The Influence of Cascading, E-Planning, and E-Budgeting on the Effectiveness of Budget Absorption in Bekasi City Government Agencies: Human Resource Competence in Financial Management as a Mediating Variable and Budget Planning Quality as a Moderating Variable - Idel Eprianto; Jhonni Sinaga (International Journal of Applied Business and International Management, 2025)
Budget absorption in local government agencies (OPDs) is often hindered by delays in implementation at the beginning of the year and a concentration of spending at the end of the year, thereby reducing program effectiveness. This study aims to analyze the influence of cascading, e-planning, and e-budgeting on the effectiveness of budget absorption, with the competence of financial management personnel as the mediating variable and the quality of budget planning as the moderating variable. The research method employs a quantitative approach using Structural Equation Modeling (SEM) based on SmartPLS. Data were collected via a questionnaire administered to local government agencies in the City of Bekasi. Results of the outer model test indicate that all constructs are valid and reliable (factor loadings 0.70; AVE 0.50; CR 0.80; HTMT 0.90). R² values of 0.68 for budget absorption effectiveness and 0.62 for planning quality indicate a strong explanatory power of the model. Hypothesis testing results prove that cascading, e-planning, and e-budgeting have a positive effect on budget absorption effectiveness. Human resource competency acts as a significant mediator, while planning quality strengthens the relationship between human resource competency and budget absorption effectiveness. This study confirms that budget absorption effectiveness depends not only on digital systems but also on strengthening human resource capacity and planning quality.